2008
DOI: 10.1016/j.febslet.2008.02.034
|View full text |Cite
|
Sign up to set email alerts
|

Transthyretin binding to A‐Beta peptide – Impact on A‐Beta fibrillogenesis and toxicity

Abstract: It has been suggested that transthyretin (TTR) is involved in preventing A-Beta fibrillization in AlzheimerÕs disease (AD). Here, we characterized the TTR/A-Beta interaction by competition binding assays. TTR binds to different A-Beta peptide species: soluble (Kd, 28 nM), oligomers and fibrils; diverse TTR variants bind differentially to A-Beta. Transmission electron microscopy (TEM) analysis demonstrated that TTR is capable of interfering with A-Beta fibrillization by both inhibiting and disrupting fibril for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
146
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(156 citation statements)
references
References 35 publications
9
146
1
Order By: Relevance
“…In vitro studies have shown that TTR binds soluble Ab and prevents Ab amyloid fibril formation (53). In 2008, the Ab-TTR interaction was further characterized and it was shown that the inhibition/disruption of Ab fibrils by TTR could be one possible mechanism underlying the protective role of TTR in AD (54). Interestingly, as for apoA-I, further investigation on the TTR-Ab interaction revealed that TTR was able to cleave Ab.…”
Section: Ttr Binding To Lipoproteins and The Identification Of Apoa-imentioning
confidence: 99%
“…In vitro studies have shown that TTR binds soluble Ab and prevents Ab amyloid fibril formation (53). In 2008, the Ab-TTR interaction was further characterized and it was shown that the inhibition/disruption of Ab fibrils by TTR could be one possible mechanism underlying the protective role of TTR in AD (54). Interestingly, as for apoA-I, further investigation on the TTR-Ab interaction revealed that TTR was able to cleave Ab.…”
Section: Ttr Binding To Lipoproteins and The Identification Of Apoa-imentioning
confidence: 99%
“…Recently, the proteolytic activity of TTR was discovered and its participation in the biology of the nervous system and high density lipoprotein (HDL) was demonstrated 8,9 . The cleavages of its particular substrates including amyloid β peptide (Aβ) and amidated neuropeptide Y (NPY) can lead to the protection of amyloidogenesis and the enhancement of nerve cell regeneration [10][11][12] . On the other hand, the TTR cleavage on apolipoprotein A-I (apoAI) promotes cholesterol efflux and increases amyloidogenicity of apoAI 13 .…”
Section: Introductionmentioning
confidence: 99%
“…TTR has therefore been suggested to generally slow AD progression. TTR appears to be a major A␤-sequestering protein in human CSF, inhibiting and even reverting the formation of amyloid fibrils, as well as reducing their toxicity in vitro (58,59). TTR forms a complex with A␤ monomers/dimers, with stronger binding affinity observed for the more structurally flexible S85A TTR mutant (60), reinforcing the idea that less structured forms of amyloid proteins may be more likely to engage in cross-amyloid interactions.…”
Section: Transthyretinmentioning
confidence: 78%